PENGARUH AKTIVITAS DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN OTOMOTIF DAN KOMPONENNYA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Khairil Akbar; Fariyanti Fariyanti; Hida Yanti (Jurnal Eksis, 2019)
This study aims to determine the partial effect and simultaneous effect of activity and liquidity on profitability in a case study of automotive companies and components listed on the Indonesia Stock Exchange in 2016-2018. The method used in this research is quantitative method. The data that has been collected is analyzed by the method of data analysis which first tests the classical assumptions before testing the hypothesis. Hypothesis testing in this study uses multiple linear regression with t test, F test and the coefficient of determination test (R2) at the level of significance of 5% (0.05). The results of the study concluded that activity partially has a significant positive effect on profitability while liquidity has a significant negative effect on profitability. And simultaneous positive and significant impact on profitability. Keywords: Activity, liquidity, profitability.